The Potential Effects of Species Ocimum basilicum L. on Health: A Review of the Chemical and Biological Studies - Brandão, Lethicia Barreto; Santos, Lizandra Lima; Martins, Rosany Lopes; Rodrigues, Alex Bruno Lobato; Costa, Anderson Luiz Pena da; Faustino, Cleidjane Gomes; Almeida, Sheylla Susan Moreira da Silva de (Pharmacognosy Reviews)
Ocimum basilicum Linn is a plant widely found throughout Brazil, popularly known as “Manjerição”, it is widely used by the world for medicinal purposes as an agent against rheumatism, headache, hepatitis, and as a diuretic. This research was carried out using databases for thesis, dissertations databases, and articles from indexed journals. This is an integrative literature review, to answer the question: “Does the species Ocimum basilicum have biological effects/activities?”. Searches were performed in the National Library of Medicine (PubMed), Virtual Health Library (VHL), CAPES, and Scopus journals, in Portuguese and English. A morphometric study of O. basilicum leaves was found in the literature. Analyzes revealed different morphological and anatomical patterns. The study of morphology is important in the medicinal activity of the plant since the secondary metabolites in plants are affected by different biotic and abiotic stresses. Thus, stress conditions affect secondary metabolites or so-called active ingredients and other compounds that plants produce, which are often the basis of their medicinal activity. According to the literature, several classes of secondary metabolites were found, such as anthraquinones, flavonoids, terpenoids, and others in the leaves of the species. The recent pieces of evidence indicate that secondary metabolites of the species O. basilicum have proven biological activities in antimicrobial, antifungal, antioxidant, allelopathic and biocide
Keywords: Manjerição; Bioactivity; Oil essential; Lamiaceae; Alfavaca